DEVELOPMENT OF A FOUNDATION FOR A KANSAS AGRICULTURAL EMERGENCY RESPONSE CORPS (KAERC) - De Los Santos, Priscilla Rose (My University, 2015)
The safety, health and well-being of animals are critical to the safety, health and well-being of humans. Public health emergencies can range from unpredictable and uncontrollable natural disasters, to man-made bioterrorism threats. Public health emergencies also include livestock disease outbreaks resulting in the loss of large numbers of livestock and agricultural products, a decrease in food quality and security and potentially result in devastating human health consequences. For these reasons, it is important to implement an Agricultural Emergency Response Corps to limit the detrimental effects to both humans and animals that can potentially occur from these emergencies, particularly those involving the emergence of a foreign animal disease (FAD). Currently, there are many active state animal emergency response teams across the country. They are strictly volunteer-based and focus almost solely on veterinary participation. This project is the foundation for development of a well-rounded team of individuals who will be trained to respond quickly and efficiently to an emergency. The goal of the Kansas Agricultural Emergency Response Corps (KAERC) is to create an all-encompassing unit with a wide range of expertise to cover all the facets of a public health emergency relating to animals, as well as overall human health. The final product is a draft of a white paper to be submitted for government approval along with a tentative list of detailed position descriptions and roles that would best benefit the initial framework of the corps. The KAERC will fall under the Kansas Department of Agriculture.
Keywords: One Health; Agricultural Emergency; Response Team; KAERC; Public Health (0573)